Splenic lymph follicles generate immunoglobulin M‐producing B cells in primary biliary cirrhosis. Issue 10 (7th January 2014) - Kikuchi, Kentaro; Tsuneyama, Koichi; Yamada, Hanae; Kajiyama, Yusuke; Matsumoto, Kotaro; Tsunashima, Hiromichi; Yamashita, Risa; Takai, Atsuko; Negishi, Masatsugu; Hara, Masumi; Moritoki, Yuki; Miyakawa, Hiroshi
<x xml:space="preserve">Abstract</x> Aim To reveal the site of immunoglobulin (Ig)M production in primary biliary cirrhosis (PBC) we performed immunohistochemical analysis on spleens collected from patients with PBC. Methods Splenic tissue samples were collected at the time of the autopsy from patients with hepatic failure. Immunostaining for IgM, CD21 and CXCL13 were performed using the splenic tissue samples. Results The samples from five out of eight cases with PBC but not in eight cases of chronic hepatitis C virus infection showed accumulation of IgM positive cells in CD21 positive lymph follicles. The CXCL13 positive cells also accumulated in the center of the lymph follicles where the IgM positive cells accumulated. Conclusion The present results suggest that excess IgM is produced from the spleen of PBC. Furthermore, it was suggested that CXCL13 positive follicular dendritic cells possibly contribute to this process.